#TITLE_ALTERNATIVE# - SURYA GURITNO (NIM: 10304001), COMETTA
There are some reliable methods to detect the existence of extrasolar planets. One of these methods is by analyzing the transit photometric light curve. When an extrasolar planet transits across its stellar disk, the star's total flux will decrease. This transiting event will create a light curve. By analyzing this light curve, one can derive some physical parameters on the star-planet system. Seager and Mallen-Ornelas (2002) have derived some equations to calculate the system parameters from light curve alone. By imposing some assumptions, they may suggest a unique solution through simulation testing. Furthermore, the limb darkening phenomenon could change considerably the shape of light curve. Consequently, to derive the system parameters properly, we should take into account this phenomenon. In this work, we adopt a model derived by Mandel and Algol (2002). Their light curve simulation code is used in this work to analyze some data. Observations plannned during this work were unfortunately unsuccessful. So we took some published data to analyze light curves accounting for limb darkening effects. For comparison, we took observational data of HD209458 from Charbonneau et al. (1998) and Brown et al. (2002) and then fitted both data using the simulated curves. The fit result showed that the Mandel-Agol simulation model prove to be very useful in helping further analysis, in which the limb darking effect cannot be neglected.